The Effectiveness of the Sex Education Package on the Body-esteem in Elementary School Children - Hamideh Zahedi; AmirHoshang mehryar; Nadereh Sohrabi; Maryam Zarnaghash (Iranian Journal of Educational Research)
Objective: The primary objective of this research endeavor was to examine the efficacy of a sex education program in enhancing the body-esteem of young students in elementary school. Methods: This study adopted an experimental approach, employing a pre-test-post-test design with a control group. The statistical population encompassed all girls attending primary schools in Shiraz during the academic year of 2021. Through random sampling, a total of 30 female students were selected, divided equally into an experimental group and a control group, comprising 15 students each. To assess body-esteem, the Body-Esteem Scale (Franzoi & Shields, 1984) was utilized. Results: The results of the covariance analysis revealed that the F statistic for the body-esteem variable attained a significant level of 0.001. This finding indicates that the implementation of the sex education package for elementary school children has exerted a positive and significant impact on their body-esteem. Conclusions: In summary, the outcomes of this study underscore the efficacy of sex education in terms of its influence on the emotional and affective outputs in primary school students.